1993
DOI: 10.3354/meps096189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coral bleaching on tissue regeneration potential and colony survival

Abstract: We assessed the influence of coral 'bleaching on the regenerative potential of corals in a senes of field expenments with artificial lesions on colony surfaces These lesions were made d u n n g a mass bleaching event in 1990 on normally coloured and bleached colonies of 3 species A4ontastrea annulans, the main reef-building coral in the Caribbean P o r~t e s astreo~des, a relatively conmon and opportunistic coral, and M e a n d r~n a meandntes, a species common on the deeper reef slope Regeneration charactensh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
2
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(83 citation statements)
references
References 21 publications
1
78
2
2
Order By: Relevance
“…Consequently, colony size was often thought not to carry much information because size was reported to be unrelated to age (but see Babcock 1991, Soong 1993. However, our studies of regeneration of coral tissue lesions (Bak 1983, Meesters & Bak 1993 and surveys of partial mortality in the field show that the processes are more complicated. In massive coral colonies most partial mortality occurs as very small lesions that are regenerated within a few days.…”
mentioning
confidence: 51%
“…Consequently, colony size was often thought not to carry much information because size was reported to be unrelated to age (but see Babcock 1991, Soong 1993. However, our studies of regeneration of coral tissue lesions (Bak 1983, Meesters & Bak 1993 and surveys of partial mortality in the field show that the processes are more complicated. In massive coral colonies most partial mortality occurs as very small lesions that are regenerated within a few days.…”
mentioning
confidence: 51%
“…In fact, in studies where experimental damage to coral tissue was inflicted in the absence of an abiotic or biotic stressor, coral tissue regenerated and overgrew algae that initially had colonized the lesions, suggesting competitive superiority of otherwise healthy coral tissue (Meesters and Bak 1993, Meesters et al 1994, van Woesik 1998. While explicit tests of the physiological effects of sedimentation and low flow on massive Porites were not conducted, their separate negative effects are well-documented and suggest that reductions in metabolism, growth, and survival could have major implications for coralalgal competitive outcomes (Dodge & Vaisnys 1977, Dallmeyer et al 1982, Dodge & Lang 1983, Hubbard & Scaturo 1985, Tomascik & Sander 1985, Hubbard et al 1987, Fabricius 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when the coral loses its zooxanthellae, it loses its main energy resource, putting at risk its essential biological functions (Hoegh-Guldberg 1999;Wilkinson 1999Wilkinson , 2000. Reduced proteins and lipids (Porter et al 1989;Michalek-Wagner & Willis 2001), lowered growth rate (Goreau & Macfarlane 1990), lower calcification and repair capabilities (Glynn 1993;Meesters & Bak 1993) and termination of gametogenesis (Szmant & Gassman 1990;Ward 2000;Fine et al 2001) have all been reported following reduction in zooxanthellae densities (bleaching). Coral bleaching, the disruption of the symbiotic association between coral hosts and their symbiotic photosynthetic algal endosymbionts, is often linked to elevated seawater temperature (Glynn 1991(Glynn , 1993Brown 1997;Hoegh-Guldberg 1999) and high solar irradiance (Jokiel 1980;Lesser et al 1990;Gleason & Wellington 1993;Glynn 1993).…”
Section: Introductionmentioning
confidence: 99%